The Rationality as Ideal. An Elsterian Approach - Vázquez Parra, José Carlos (2017)
From a philosophical theory perspective, a speech of irrationality of actions is not new. Though, rationality is an ideal not a rule. It challenges traditional paradigms of the explanatory power of rational action. Elsterian proposal of rationality seeks proposing a new vision of rationality of actions taking into account those occasions in which behaviors are considered to be rational, though they are not. This aspect of rationality of actions, enquiries the possibility of acting rationally, a doubt of the explanatory power that has sustained the rationality in the different theories of actions.